PENGARUH METODE PENGOMPOSAN LANGSUNG DENGAN JENIS FESES TERNAK BERBEDA TERHADAP PERTUMBUHAN RUMPUT ZANZIBAR - Saputra, Fahrian; Yani, Ahmad; Amrullah, Amrullah; Budiman, Cecep; Hamdani, Asrul; Wahyu Satria, Edi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mombaca grass is a type of forage plant with good nutritional composition and is widely used by livestock farmers in Indonesia. This study aimed to determine the effect of providing different types of livestock feces on the growth of mombaca grass. The study was conducted from January to March 2026 using a randomized block design with four treatments and four groups. Data analysis was performed using analysis of variance for plant height, leaf length, leaf width, stem diameter, and number of tillers. The results showed that the highest average values for all variables, such as plant height, ranged from 19.51 to 34.54 cm/2 weeks, leaf length from 15.86 to 21.77 cm/2 weeks, leaf width from 5.93 to 8.93 cm/2 weeks, stem diameter from 1.22 to 1.61 cm/2 weeks, and number of tillers from 197 to 2.42 cm/2 weeks.